Data from: Circadian periodicity in space use by ungulates of temperate regions: how much, when, and why? - Peron, Guillaume; Duparc, Antoine; Garel, Mathieu; Marchand, Pascal; Morellet, Nicolas; Said, Sonia; Loison, Anne (Dryad, 2019)
1. When they visit and revisit specific areas, animals may reveal what
they need from their home range and how they acquire information. The
temporal dimension of such movement recursions, i.e., periodicity, is
however rarely studied, yet potentially bears a species, population, or
individual-specific signature. 2. A recent method allows estimating the
contribution of periodic patterns to the variance in a movement path. We
applied it to 709 individuals from 5 ungulate species, looking for species
signatures in the form of seasonal variation in the intensity of circadian
patterns. 3. Circadian patterns were commonplace in the movement tracks,
but the amount of variance they explained was highly variable among
individuals. It increased in intensity during spring and summer, when key
resources were spatially segregated, and decreased during winter, when
food availability was more uniformly low. Other periodicity-inducing
mechanisms supported by our comparison of species- and sex-specific
patterns involve young anti-predator behavior, territoriality, and
behavioral thermoregulation. 4. Model-based continuous-time movement
metrics represent a new avenue for researchers interested in finding
individual-, population-, or species-specific signatures in heterogeneous
movement databases featuring various study designs and sampling
resolutions. However, we observed large amounts of individual variation,
so comparative analyses should ideally use both GPS and animal-borne
loggers to augment the discriminatory power; and be based on large
samples. We briefly outline potential uses of the intensity of circadian
patterns as a metric for the study of animal personality and community
ecology.
eta parameter valuesThis file contains the parameter estimates used to
draw Fig. 2Eta for Dryad.csv
Keywords: Capra ibex; Environmental cycles; ovis musimon; Cervus elaphus; spectral analysis; rupicapra rupicapra; Capreolus capreolus